Nitrogen-Doped Carbon Encapsulated Partial Zinc Stannate Nanocomposite for High-Performance Energy Storage Materials - Yu, Jiage; Liu, Zhijie; Zhang, Xian; Ding, Yu; Fu, Zhengbing; Wang, Feng (Frontiers in Chemistry, 2021)
As a bimetal oxide, partial zinc stannate (ZnSnO3) is one of the most promising next-generation lithium anode materials, which has the advantages of low operating voltage, large theoretical capacity (1,317 mA h g−1), and low cost. However, the shortcomings of large volume expansion and poor electrical conductivity hinder its practical application. The core-shell ZnSnO3@ nitrogen-doped carbon (ZSO@NC) nanocomposite was successfully obtained by coating ZnSnO3 with polypyrrole (PPy) through in situ polymerization under ice-bath conditions. Benefiting from this unique compact structure, the shell formed by PPy cannot only effectively alleviate the volume expansion effect of ZnSnO3 but also enhance the electrical conductivity, thus, greatly improving the lithium storage performance. ZSO@NC can deliver a reversible capacity of 967 mA h g−1 at 0.1 A g−1 after 300 cycles and 365 mA h g−1 at 2 A g−1 after 1,000 cycles. This work may provide a new avenue for the synthesis of bimetal oxide with a core–shell structure for high-performance energy storage materials.